Analisis Efektivitas Penerapan Pemutihan Pajak Kendaraan Bermotor Bagi Masyarakat Di Kabupaten Toraja Utara - Tiara Patari; Nurasyiah; Fajriani Azis (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study aims to analyze the effectiveness of the implementation of motor vehicle tax amnesty for the community in North Toraja Regency and to explain and identify obstacles in the implementation of motor vehicle tax amnesty in North Toraja Regency. The data collection techniques used were interviews and documentation. The data analysis technique used in this study was descriptive qualitative. The results of this study indicate that the Effectiveness of the Implementation of Motor Vehicle Tax Amnesty for the Community in North Toraja Regency using 5 effectiveness indicators used to measure how effective the implementation of tax amnesty for the community shows positive results or is quite effective. However, in its implementation there are still several obstacles that are expected to be overcome immediately by the relevant parties so that the implementation of motor vehicle tax amnesty in North Toraja Regency is even more effective.